How Is the Fear of War Impacting Italian Young Adults' Mental Health? The Mediating Role of Future Anxiety and Intolerance of Uncertainty - Giorgio Maria Regnoli; Gioia Tiano; Barbara De Rosa (MDPI AG, 2024)
The Russian-Ukrainian conflict is affecting mental health even in communities that are not directly involved in the war; added to this is the escalating conflict in the Middle East and its dangerous spread, which brings the war back to the center of the contemporary social and economic horizon. The present study aims to explore the psychological impact of war in a sample of 310 Italian young adults (18-30 years; M = 22.0; SD = 2.6) while exploring the relationship between Fear of War and psychological distress and evaluating the mediating effects of Future Anxiety and Intolerance of Uncertainty in this relation. Findings highlighted how Fear of War positively and significantly affects Stress, Anxiety, and Depression, and, at the same time, how it fuels both Future Anxiety and Intolerance of Uncertainty. These constructs, in addition to positively affecting the mental health outcomes considered, mediate the relationship between Fear of War and youth psychological distress with a significant indirect effect observed in all three mediation models performed. Finally, significantly higher levels of psychological distress, Fear of War, and Future Anxiety are reported in women than in men. The findings are discussed with reference to the recent literature on the psychological impact of war and on contemporary youth psychological distress, indicating the importance of educational policies and targeted interventions aimed at supporting this target in coping with multiple contemporary collective stressors.